Neurodevelopmental disorders (NDD) without boundaries: research and interventions beyond classifications - Louveau, Cécile; Ellul, Pierre; Iftimovici, Anton; Dubreucq, Julien; Laidi, Charles; Leyrolle, Quentin; Purper-Ouakil, Diane; Jacquemont, Sebastien; Lyonnet, Stanislas; Barthélémy, Catherine; Krebs, Marie-Odile; Bai, Jing; et al. (Journal of Neural Transmission, 2023)
On June 2022, the 2nd Webinar “Neurodevelopmental Disorders (NDD) without boundaries took place at the Imagine Institute in Paris and was broadcasted live and in replay. The aim of this webinar is to address NDD in a dimensional rather than in a categorical approach. Several speakers were invited to present their researches on the subject. Classifications in NDD were discussed: irritability in NDD, involvement of the immune system in neurodevelopment, nutrition and gut microbiota modulate brain inflammation and neurodevelopment, co-occurring conditions in autistic adolescents and adults without intellectual disability. Classifications in psychiatric disorders were asked: mapping the effect of genes on cognition and autism risk, epigenetics and symptomatic trajectory in neurodevelopmental disorders, the autism-schizophrenia continuum in two examples: minor neurological signs and EEG microstates, the cerebellum in schizophrenia and autism: from imaging to intervention perspectives. Both genetic and environmental factors, along with clinical and imaging features, argue toward a continnum between NDD but also with adult psychiatric presentations. This new paradigm could modify the therapeutic strategy, with the development of large-spectrum treatments or new psychotherapies addressing co-occuring symptoms. The complexity and the heterogeneity of NDD apply well to the next scientific and political challenges: developing international convergence to push back the frontiers of our knowledge. This article is a summary of the 2nd webinar “Neurodevelopmental Disorders (NDD) without boundaries: research and interventions beyond classifications” sponsored by the French National Academy of Medicine, the autism and neurodevelopmental disorders scientific interest group (GIS), the International Research Network Dev-O-Psy and the French Institute of Psychiatry (GDR3557). Oral presentations are available as a replay on the following website (in French): https://autisme-neurodev.org/evenements/2022/04/12/tnd-sans-frontieres-la-recherche-et-les-interventions-au-dela-des-classifications/ .